2017
DOI: 10.1016/j.mjafi.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Use of corticosteroids in acute respiratory distress syndrome: Perspective from an Indian intensive care unit

Abstract: m e d i c a l j o u r n a l a r m e d f o r c e s i n d i a 7 3 ( 2 0 1 7 ) 1 1 8 -1 2Methods: This was a retrospective study at an Indian intensive care unit (ICU) on ARDS patients. Demographic, clinical, laboratory, and imaging parameters were collected. Patients were divided into cohorts based on steroid use, and some received high-dose (2 mg/kg/day), whereas others received low-dose (1 mg/kg/day) steroids. Primary outcomes were in-hospital mortality and secondary outcomes included need for and duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[5][6][7] Findings in animal studies have aroused great interest in assessing the efficacy of glucocorticoids in ARDS patients. However, different studies have drawn different conclusions; some researchers found that administration of glucocorticoids was associated with better prognosis in ARDS patients, [8][9][10][11][12][13][14] while other studies did not support the routine use of glucocorticoids for ARDS [15][16][17][18][19][20] ; thus, the effect of glucocorticoids in treating ARDS patients remains unclear, and there are contradictions between different guidelines on the use of corticosteroids for ARDS patients. 21,22 Recently, the largest randomized controlled trials (RCTs) published to date found that the administration of glucocorticoids could significantly improve the prognosis of moderate-to-severe ARDS patients (reducing the duration of mechanical ventilation and mortality) without increasing the incidence of adverse events (including hyperglycaemia and infectious complication events).…”
mentioning
confidence: 99%
“…[5][6][7] Findings in animal studies have aroused great interest in assessing the efficacy of glucocorticoids in ARDS patients. However, different studies have drawn different conclusions; some researchers found that administration of glucocorticoids was associated with better prognosis in ARDS patients, [8][9][10][11][12][13][14] while other studies did not support the routine use of glucocorticoids for ARDS [15][16][17][18][19][20] ; thus, the effect of glucocorticoids in treating ARDS patients remains unclear, and there are contradictions between different guidelines on the use of corticosteroids for ARDS patients. 21,22 Recently, the largest randomized controlled trials (RCTs) published to date found that the administration of glucocorticoids could significantly improve the prognosis of moderate-to-severe ARDS patients (reducing the duration of mechanical ventilation and mortality) without increasing the incidence of adverse events (including hyperglycaemia and infectious complication events).…”
mentioning
confidence: 99%
“…[5,6] However, previous randomized trials failed to provide convincing evidence of consistent results in favor of corticosteroid therapy . [7][8][9] They demonstrated that corticosteroids have advantages over controls in reducing ARDS mortality, the duration of mechanical ventilation, and the length of hospital stay. The MIMIC-III database includes real-world clinical data, reflecting the diversity of actual clinical practice, and offers broad sample coverage with extensive patient data, making it advantageous for rare disease and subgroup analyses.…”
Section: Introductionmentioning
confidence: 99%